Human topoisomerase II alpha as a prognostic biomarker in cancer chemotherapy - Ali, Yousaf; Abd Hamid, Shafida (Springer, 2016)
Topoisomerases are nuclear enzymes that regulate topology of DNA by facilitating the temporary cleavage and ligation cycle of DNA. Among all forms of topoisomerases, TOP-IIA is extensively associated with cell proliferation and therefore is an important therapeutic target in diseases that involved cellular proliferation such as cancers. Nearly half of present-day antitumor regimens contain at least one prescription that act as a topoisomerase inhibitor. Generally, tumor cells show divergent expression of TOP-IIA compared to normal cells. The remarkable expression of TOP-IIA in various carcinomas provides a significant biomarker toward understanding the nature of malignancy. TOP-IIA expression and amplification studies help in diagnosing cancer and to observe the disease progression, overall survival (OS) of patients, and response to therapy. This review highlights the research output and analysis in exploring the standing of TOP-IIA in various carcinomas. As some reports show contradiction within the same field of interest, the outline of that may help to induce researchers for further investigation and clarification. To the best of our knowledge, this is the first overview briefly summarizing the prognostic feature of TOP-IIA in various types of cancer.